Triple crown - Francis, Felix (G.P. Putnam's Sons, 2016)
"Jefferson Hinkley is back in the newest thriller in the Dick Francis tradition, this time on a special mission to the United States to investigate a conspiracy involving the biggest horse races in the country. Jeff Hinkley, investigator for the British Horseracing Authority, has been seconded to the US Federal Anti-Corruption in Sports Agency (FACSA) where he has been asked to find a mole in their organization--an informant who is passing on confidential information to those under suspicion in American racing. At the Kentucky Derby, Jeff joins the FACSA team in a raid on a horse trainer's barn at Churchill Downs, but the bust is a disaster, and someone ends up dead. Then, on the morning of the Derby itself, three of the most favored horses in the field fall sick. These suspicious events can be no coincidence. In search of answers, Jeff goes undercover as a groom on the backstretch at Belmont Park racetrack in New York. But he discovers far more than he was bargaining for: corrupt individuals who will stop at nothing--including murder--to capture the most elusive prize in world sport, the Triple Crown"--